The role of miRNAs in regulation of platelet activity and related diseases - a bioinformatic analysis. (3rd October 2022) - Wicik, Zofia; Czajka, Pamela; Eyileten, Ceren; Fitas, Alex; Wolska, Marta; Jakubik, Daniel; von Lewinski, Dirk; Sourij, Harald; Siller-Matula, Jolanta M.; Postula, Marek
Abstract: MicroRNAs (miRNAs) are small, non-coding RNAs, able to regulate cellular functions by induction of mRNA degradation and post-transcriptional repression of gene expression. Platelets are the major source of circulating miRNAs, with significant regulatory potential on cardiovascular pathophysiology and other diseases. MiRNAs have been shown to modify the expression of platelet proteins, which influence the platelets reactivity. Circulating miRNAs can be determined from plasma, serum, or whole blood, and they can be used as diagnostic and prognostic biomarkers as well as therapeutic targets including cardiovascular diseases (CVDs). Herein, we present original results from bioinformatic analyses, which identified top 22 platelet-related miRNAs including hsa-miR-320a, hsa-miR-16-5p, hsa-miR-106a-5p, hsa-miR-320b, hsa-miR-15a-5p, hsa-miR-15b-5p, hsa-miR-195-5p, hsa-miR-92a-3p as widely involved in platelet reactivity and associated diseases, including CVDs, Alzheimer's and cerebrovascular diseases, cancer and hypertension. Analysis focused on the identification of the highly regulatory targets shared between those miRNAs identified 43 of them. Best ranked genes associated with overall platelet activity and most susceptible for noncoding regulation were PTEN, PIK3R1, CREB1, APP, and MAPK1. Top targets also strongly associated with CVDs were VEGFA, IGF1, ESR1, BDNF, and PPARG. Top targets associated with other platelet-related diseases including cancer identified in our study were TP53, KRAS, and CCND1. The most affected pathways by top miRNAs and top targets included diseases of signal transduction by Growth Factor Receptors (GDFRs) and second messengers, platelet activation, signaling, and aggregation, signaling by VEGF, MAPK family signaling cascades, and signaling by Interleukins. Terms specific only for platelet-related miRNAs included coronary artery disease, platelet degranulation, and neutrophil degranulation, while for the top platelet-related genes it was Estrogen Signaling Receptor (ESR) mediated signaling, extra-nuclear estrogen signaling, and endometriosis. Our results show the novel features of platelet physiology and may provide a basis for further clinical studies focused on platelet reactivity. They also show in which aspects miRNAs can be promising biomarkers of platelet-related pathological processes.